Engineering of CH3NH3PbI3 Perovskite Crystals by Alloying Large Organic Cations for Enhanced Thermal Stability and Transport Properties. Issue 36 (28th July 2016) - Peng, Wei; Miao, Xiaohe; Adinolfi, Valerio; Alarousu, Erkki; El Tall, Omar; Emwas, Abdul‐Hamid; Zhao, Chao; Walters, Grant; Liu, Jiakai; Ouellette, Olivier; Pan, Jun; Murali, Banavoth; et al.
Abstract: The number of studies on organic–inorganic hybrid perovskites has soared in recent years. However, the majority of hybrid perovskites under investigation are based on a limited number of organic cations of suitable sizes, such as methylammonium and formamidinium. These small cations easily fit into the perovskite's three‐dimensional (3D) lead halide framework to produce semiconductors with excellent charge transport properties. Until now, larger cations, such as ethylammonium, have been found to form 2D crystals with lead halide. Here we show for the first time that ethylammonium can in fact be incorporated coordinately with methylammonium in the lattice of a 3D perovskite thanks to a balance of opposite lattice distortion strains. This inclusion results in higher crystal symmetry, improved material stability, and markedly enhanced charge carrier lifetime. This crystal engineering strategy of balancing opposite lattice distortion effects vastly increases the number of potential choices of organic cations for 3D perovskites, opening up new degrees of freedom to tailor their optoelectronic and environmental properties. Abstract : Despite its large ionic radius, ethylammonium can partially replace methylammonium in the widely studied 3D hybrid perovskites CH3 NH3 PbI3 . This partial replacement results in higher crystal symmetry, improved material stability, and markedly enhanced photocarrier lifetime of the alloy perovskites.